Dual Role of Natural Killer Cells on Graft Rejection and Control of Cytomegalovirus Infection in Renal Transplantation - López-Botet, Miguel; Vilches, Carlos; Redondo-Pachón, Dolores; Muntasell, Aura; Pupuleku, Aldi; Yélamos, José; Pascual, Julio; Crespo, Marta (Frontiers in Immunology, 2017)
Allograft rejection constitutes a major complication of solid organ transplantation requiring prophylactic/therapeutic immunosuppression, which increases susceptibility of patients to infections and cancer. Beyond the pivotal role of alloantigen-specific T cells and antibodies in the pathogenesis of rejection, NK cells may display alloreactive potential in case of mismatch between recipient inhibitory killer-cell immunoglobulin-like receptors (KIR) and graft HLA class I molecules. Several studies have addressed the impact of this variable in kidney transplant with conflicting conclusions; yet, increasing evidence supports that alloantibody-mediated NK cell activation via FcγRIIIA (CD16) contributes to rejection. On the other hand, human cytomegalovirus (HCMV) infection constitutes a risk factor directly associated to the rate of graft loss and reduced host survival. The levels of HCMV-specific CD8+ T cells have been reported to predict the risk of post-transplant infection, and KIR-B haplotypes containing activating KIR genes have been related with protection. HCMV infection promotes to a variable extent an adaptive differentiation and expansion of a subset of mature NK cells which display the CD94/NKG2C activating receptor. Evidence supporting that adaptive NKG2C+ NK cells may contribute to control the viral infection in kidney transplant recipients (KTR) has been recently obtained. The dual role of NK cells in the interrelation of HCMV infection with rejection deserves attention. Further phenotypic, functional and genetic analyses of NK cells may provide additional insights on the pathogenesis of solid organ transplant complications, leading to the development of biomarkers with potential clinical value.